2005
DOI: 10.1002/ajmg.a.30998
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromatosis von Recklinghausen type I phenotype and early onset of cancers in siblings compound heterozygous for mutations in MSH6

Abstract: We report on a nonconsanguineous family in which two siblings with cutaneous manifestations leading to a diagnosis of neurofibromatosis type 1 (NF1) developed CNS tumors at an early age. In addition, one of them developed a T-cell lymphoma. Neither parent had NF1. The mother was known to be heterozygous for a MSH6 mutation, and the father was found to be heterozygous for a different MSH6 mutation. Screening of MSH2, MLH1, MSH6, PMS1, PMS2, and MLH3 in the affected children disclosed that they both were compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 34 publications
1
46
0
Order By: Relevance
“…Because the MMR genes mlh1, msh2, and msh6 are known to play a role in class switch recombination (49)(50)(51)(52), it is tempting to speculate that their deficiency can directly lead to immune malignancies, without the need for creating a genomic instable situation that mutates other tumor suppressors. The fact that some patients with biallelic MMR inactivation were reported to be IgA-deficient supports this idea (11). Also, MMR-deficient mice show a reduction in isotype switching (49,50,52).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Because the MMR genes mlh1, msh2, and msh6 are known to play a role in class switch recombination (49)(50)(51)(52), it is tempting to speculate that their deficiency can directly lead to immune malignancies, without the need for creating a genomic instable situation that mutates other tumor suppressors. The fact that some patients with biallelic MMR inactivation were reported to be IgA-deficient supports this idea (11). Also, MMR-deficient mice show a reduction in isotype switching (49,50,52).…”
Section: Discussionmentioning
confidence: 89%
“…In the years following the discovery of HNPCC, continuous monitoring of HNPCC families has revealed several cases of humans with innate inactivating mutations in both alleles of a MMR gene, resulting from inbreeding or coincidence (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). These patients lack the MMR protein from the beginning and therefore develop cancer at extremely early ages, generally before the age of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…[32][33][34] Children with CMMRD syndrome are known to manifest CALMs and axillary freckling. 35 Few cases have been reported in the literature and therefore the full phenotypic spectrum or the expressivity of CMMRD syndrome is not known.…”
Section: Genetic Modifier For Cancer In Gaucher Disease 4737mentioning
confidence: 99%
“…Péron et al 2 have shown in 3 CMMR-D patients that 15,19,20 . It remains to be seen whether defective IgA and IgG production is a common feature of CMMR-D. Fortunately, severe bacterial infections have not been reported to occur at high frequencies in persons with CMMR-D.…”
mentioning
confidence: 99%